2020
DOI: 10.1029/2020gl087467
|View full text |Cite
|
Sign up to set email alerts
|

Relative Roles of Low‐Level Wind Speed and Moisture in the Diurnal Cycle of Rainfall Over a Tropical Island Under Monsoonal Flows

Abstract: Using satellite observations and reanalysis data, this study investigates the relative roles of low-level wind speed and moisture content in the rainfall diurnal cycle over a tropical island influenced by monsoonal winds. Results show that the spatiotemporal characteristics of rainfall over the island are evidently influenced by the two factors. Specifically, the spatial distribution of rainfall is primarily determined by the low-level wind speeds, while the rainfall diurnal cycle is influenced by both factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Rao et al (2019) suggested that higher wind speed conditions over south China can support a higher occurrence of convection and also stronger diurnal variation, although they did not directly examine the diurnal amplitude of precipitation. More recently, Zhu et al (2020) showed that both sea breeze circulations and afternoon rainfall over Hainan Island could become stronger under weaker ambient wind speed at the lower level. However, whether their conclusion is applicable for the MC is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Rao et al (2019) suggested that higher wind speed conditions over south China can support a higher occurrence of convection and also stronger diurnal variation, although they did not directly examine the diurnal amplitude of precipitation. More recently, Zhu et al (2020) showed that both sea breeze circulations and afternoon rainfall over Hainan Island could become stronger under weaker ambient wind speed at the lower level. However, whether their conclusion is applicable for the MC is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the CSs initiate over the ocean in the morning (0830–1130 LT) and propagate eastward to upslope regions to mountain peak (1130–1430 LT), where it reaches the maximum at about 1430–1730 LT, and then move to leeward side 37 . The diurnal variability in CSs may be due to the diurnal cycle of solar radiation and moisture 15 , 46 , air–sea interactions 47 , 48 , or large-scale atmospheric conditions 10 , 14 . To better understand what drives the diurnal cycle in CSs occurrence over the WG, this sub-section presents the diurnal variability of large-scale atmospheric conditions like temperature, moisture, and winds etc.…”
Section: Resultsmentioning
confidence: 99%
“…With the radar observations and reanalysis data, Chen et al 10 showed that land breeze is responsible for the nocturnal rainfall maximum in China’s Pearl River Delta region during the Mei-Yu season. More recently, Zhu et al 15 noted the multiscale interactions between large-scale circulations and land-sea breeze that plays a vital role in the diurnal cycle of rainfall over the tropical islands.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid the influence of tropical cyclones, we focused the study period on the first rainy season (April‐June) in South China from 2016 to 2018. Only the days with low‐level southwesterlies were selected for analysis in order to keep the synoptic circulations consistent with the prevailing mean flows (Zhu et al., 2020). Specifically, the selected days were determined when the domain‐averaged (refer to the blue rectangle in Figure 1a) daily mean 850‐hPa horizontal winds have a direction between 200° and 250° using the ERA‐Interim reanalysis.…”
Section: Methodsmentioning
confidence: 99%
“…The island storms are demonstrated to be particularly active when this area is dominated by low-level southwesterlies (Bai et al, 2020a). Under such atmospheric circulations, a significant diurnal cycle of storms occurs in the afternoon attributable to the collision of the SBFs from different sides of the island (Zhu et al, 2017(Zhu et al, , 2020. Prior studies have suggested that the development of local circulations (e.g., SBFs, HCRs, mountain waves) can also be dramatically influenced by the ambient flows (e.g., Bennett et al, 2006;Chen et al, 2016;Fovell & Dailey, 2001;Qian et al, 2009).…”
mentioning
confidence: 99%